The Evolution of Ethical Standards in Health Research: An Islamic Overview - Ali, Bello; Sule, Muhammad Maga (Universitas Muhammadiyah Surakarta, 2024)
This review examines the intricate historical route of ethical standards within health research, integrating insights from an Islamic perspective. It meticulously traces pivotal junctures from the genesis of ethical frameworks like the Nuremberg Code and the Declaration of Helsinki to the establishment and evolution of Institutional Review Boards (IRBs). Employing content analysis, the paper examines the adaptive nature of ethical guidelines in facing contemporary challenges, including genetic research and emerging technologies, through the lens of Islamic principles. It emphasizes the dynamic interplay between ethics and progress, highlighting the pivotal role of ethical considerations in safeguarding the well-being of research participants and upholding the integrity of scientific endeavours within an Islamic ethical framework. Through this exploration, the study underscores the indispensable role of ethical foundations in steering responsible and socially conscious research practices across multifaceted domains, thereby shaping a more conscientious and accountable landscape in health research, enriched by Islamic perspectives.